Shiga Toxin–producing Escherichia coli, New Mexico, USA, 2004–2007 - Sarah Lathrop (Emerging Infectious Diseases, 2009)
Sporadic infection with Shiga toxin–producing Escherichia coli (STEC) in New Mexico increased from 0.9 cases per 100,000 population (95% confidence interval [CI] 0.5–1.36) in 2004 to 1.7 (95% CI 1.14–2.26) in 2007. Non-O157 STEC was more common in nonwhite residents, children <5 years of age, and urban residents.